Acetaldehyde production by ethanol dehydrogenation over Cu-ZnAl2O4: Effect of catalyst synthetic strategies on performances. (2nd November 2022) - Pampararo, Giovanni; Garbarino, Gabriella; Comite, Antonio; Busca, Guido; Riani, Paola
Graphical abstract: Highlights: CuO-ZnAl2 O4 based catalysts (Cu 7.4 wt%) prepared via innovative synthetic routes. unsupported Cu and CuO nanoparticles prepared and tested. new synthesis of CuO-ZnAl2 O4 by carbon-assisted solid state reaction. investigation of the support-metal interaction effect. Catalytic performances are affected by adopted preparation route. Abstract: CuO-ZnAl2 O4 based catalysts (Cu 7.4 wt%) were tested for selective dehydrogenation of ethanol to acetaldehyde. Different preparation procedures were adopted: wet and incipient-wetness impregnation using commercial ZnAl2 O4 as catalyst support, chitosan complexation, hard template, solid state and carbon-assisted solid state syntheses (SSC) starting from mixed Cu/Zn/Al precursors. Moreover, support role was investigated by synthesizing unsupported Cu and CuO nanoparticles. Catalysts show high ethanol conversion and high selectivity to acetaldehyde, whereas unsupported Cu and CuO nanoparticles appear to be poorly active in the whole temperature range. Novel Cu-SSC catalyst allows 68.8% yield in acetaldehyde at 623 K in steady state conditions even though a very high selectivity was obtained at 573 K (99.5%). Investigated catalysts can be efficiently pre-reduced directly in the reactant mixture, and they deactivate slowly at the timescale of 8 h on stream, when kept at 573 K. Apparent activation energies are in the range 100–350 kJ/mol, in excellent agreement with literature data.